Uranium recovery from laboratory wastewater in phosphoric acid medium - K. Fatemi; M. Habibi Zare; H. Vakili (مجله علوم و فنون هسته‌ای, 2020)
In SOOREH Co, a significant amount of uranium-containing phosphoric acid wastewater from analytical operations is produced on a large volume of process samples. Uranium recovery and its optimal use in the UF6 gas production cycle is the most important goal of this research. To achieve this goal, two methods for the recovery of uranium from this wastewater have been investigated. The first method is to use TBP and D2EHPA extractant diluted with kerosene. The results of this study showed that up to 98% of uranium is extracted from laboratory wastewater, 95% of which can be stripped from the organic phase by ammonium bicarbonate solution. The second method is to precipitate uranium using sodium dithionite. In this study, the two-step process of uranium recovery from phosphoric acid wastewater has been studied. The results of this method show that using sodium dithionite with two-stage precipitation, the concentration of uranium in the filtered solution of sediments is reduced to less than 0.2 ppm and this reduction in concentration is equal to the efficiency up to 99.99%. Therefore, the use of the sedimentation method to recover uranium from phosphoric acid wastewater by sodium dithionite is a more appropriate method compared to the solvent extraction method and is recommended for this type of wastewater.